Mental health among healthcare personnel during COVID-19 in Asia: A systematic review - Anucha Thatrimontrichai; David J. Weber; Anucha Apisarnthanarak (Journal of the Formosan Medical Association, 2021)
The COVID-19 pandemic has been associated with an insidious wave of psychological stress among healthcare personnel (HCP) in Asia. Mental exhaustion, burnout, fear, depression, anxiety, insomnia, and psychological stress among HCPs have intensified a daunting challenge during the COVID-19 pandemic. The consequences of such stress may negatively impact patient and HCP safety. This review article reports the associations of mental health status attributed to the COVID-19 pandemic among HCP and their impact on patient safety, and infection prevention and control practices during pandemics.